2017
DOI: 10.1155/2017/4612769
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Attenuates the Progression of Hepatic Fibrosis Induced by Bile Duct Ligation

Abstract: Background. The sympathetic nervous system (SNS) is responsible for hepatic stellate cells (HSCs) activation and the accumulation of collagen that occurs in hepatic fibrogenesis. Carvedilol has been widely used for the complication of hepatic cirrhosis in the clinic. Furthermore, it has powerful antioxidant properties. We assessed the potential antifibrotic effects of carvedilol and the underlying mechanisms that may further enhance its clinical benefits. Methods. Using a bile duct ligation rat model of hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…Despite this ailment is a historic disease, yet anti-fibrotic therapies are powerless to restrain liver fibrosis in an efficient approach 25 . Nevertheless, Carvedilol, a non-selective β-blocker approved for the treatment of hypertension, has been proven for its efficient hepatic anti-fibrotic properties that are mainly ascribed to its antioxidant and anti-inflammatory properties 16 , 18 , 21 . However, in our study, we have evaluated the impact of circulating miR-200a/SMAD7/TGF-β1 axis and the suppression of EMT on the anti-fibrotic effect of Carvedilol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this ailment is a historic disease, yet anti-fibrotic therapies are powerless to restrain liver fibrosis in an efficient approach 25 . Nevertheless, Carvedilol, a non-selective β-blocker approved for the treatment of hypertension, has been proven for its efficient hepatic anti-fibrotic properties that are mainly ascribed to its antioxidant and anti-inflammatory properties 16 , 18 , 21 . However, in our study, we have evaluated the impact of circulating miR-200a/SMAD7/TGF-β1 axis and the suppression of EMT on the anti-fibrotic effect of Carvedilol.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has associated the myocardial anti-fibrotic role of Carvedilol to a subtype of miRs and SMADs 19 . However, in the liver, the anti-fibrotic mechanism of Carvedilol was explained in terms of its antioxidant and anti-inflammatory properties 16 , 18 , 20 , 21 , yet the exact signaling pathways underlying its hepatic anti-fibrotic activity in the context of miR-200a, SMAD7 and EMT are still unknown, which is the aim of this work.…”
Section: Introductionmentioning
confidence: 99%
“…From our study, we found that GA could significantly reduce the accumulation of hydroxyproline content in the fibrotic liver. To confirm the effects on collagen, we next measured collagen I because originally the collagen content was estimated from the hydroxyproline content of acid hydrolysates of tissue, not collagen directly [31]. Collagen I is the most abundant and ubiquitous connective tissue protein and through Western blot showed that GA could effectively reduce the deposition of collagen I in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that carvedilol treatment attenuates liver lesions [16]. Tian et al [17] demonstrated that carvedilol can attenuate hepatic fibrosis by ameliorating oxidative stress in rats with bile duct ligation. The present study evaluated the effects of carvedilol on Ang II-induced HSC proliferation and contraction and further elucidated the underlying molecular mechanisms of its effects on liver fibrosis and portal hypertension.…”
Section: Introductionmentioning
confidence: 99%